“Heads Up Girls!” a training intervention to improve scanning behavior in youth female football - Hintermann, Mirjam; Romann, Michael; Born, Dennis-Peter; Taube, Wolfgang; Fuchslocher, Jörg (Frontiers in Sports and Active Living, 2025)
BackgroundIn football, visual exploration and scanning are crucial to make players aware of their teammates’ and their opponents’ positions, thus improving their decision-making. However, specific recommendations on systematic training methods to improve scanning behavior are limited. Therefore, this study investigated the effects of a five-week scanning-focused training intervention on scanning behavior in U19 female football players.MethodsA total of 36 female football players (mean ± SD age: 16.7 ± 1.2 years) from two elite and two grassroots teams were assigned to a control and intervention group. The intervention group completed one to two scanning-focused training sessions per week, while the control group followed their regular training routine. Scanning behavior was assessed using video analysis of 4v4 small-sided games in pre-, post-, and retention tests. A scan was defined as an active head movement, during which the player's head was directed away from the ball.ResultsThe intervention group significantly increased mean number of scans per game situation from pre- to post-test (p = 0.002), with no significant improvements in the control group (p = 0.088). However, this improvement was only observed in elite (p = 0.001), but not in grassroots players. After scanning, elite players performed more successful actions than grassroots players (p = 0.011), with no significant effect throughout the intervention period (p = 0.074). The retention test three weeks later (n = 31) showed that the increased scanning behavior of the post-test was maintained.ConclusionIn conclusion, a five-week scanning-focused training intervention improves scanning behavior in young female football players, particularly at elite level. These findings highlight the value of integrating perceptual-cognitive training into football coaching.